Read range performance of microstrip patch reader antenna for uhf rfid applications - Norzeli S.M.; Din N.M.; Ismail I.; Deros S.N.M.; Ali M.T.; Saravani S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This study conducted to compare a read range performance of microstrip patch reader antenna for UHF Radio Frequency Identification (RFID) applications. The circularly polarized reader antenna described in this study are designed to be affixed the polarization mismatch problem between reader antenna and tag antenna. Two truncated at the corner of the ordinary rectangular patch antenna is designed for UHF band (919-923 MHz) which destined for Malaysian systems. Measured results show that the antenna with size of 115*115*1.6 mm have gain antenna of 5.3 dBi, satisfactory 3-dB axial-ratio and reading range of 2m. Read range measurement results of the reader antenna design and tags antenna with the reader are observed and analysed to validate the practical performance. The reader antenna design delivered in this study areappropriate to UHF RFID applications. BEIESP.